GAMBARAN KARAKTERISTIK IBU POST PARTUM DENGAN BENDUNGAN ASI DI PMB BD I CITEREUM NEGLASARI BANDUNG - Nova Rati Lova; Della Siti Nurfalah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Background: In Indonesia in 2016, mothers with plugged duct are 76,543 (71.10%) with the highest rate of 37.12% (Kemenkes of RI, 2016). In 2016, almost 52% of breastfeeding mothers suffered from plugged duct (Dinkes of West Java, 2016). Research Method: This study employed descriptive method. Populations in this study are 40 postpartum mothers who suffered from plugged duct in private practice midwives of bd. I Ds. Neglasari, Kec Banjaran Kab. Bandung 2021. Samples used in this study were taken by total sampling. Data used in this study are secondary data using checklist (√) method that are available on the medical records in. Results: According to the data obtained from this study, respondents with the characteristic of getting plugged duct are 40 people (100%). Based on the age category, almost all respondents are between 20 to 35 years old by 33 people (82.5%). Based on the category of education, almost all respondents have got low level of education (SD, SMP) by 38 people (92.5%). Based on the category of job, half of all respondents are as housewives by 20 people (50%). Based on the category of parity, most of respondents’ the parity history is multipara by 21 people (52.50%). Conclusion: The characteristic descriptions of postpartum mothers with plugged duct are age, education, job, and parity. According to the study, it is suggested that focus on delivering information about the characteristic descriptions of postpartum mothers should be done more. It is also suggested that more varied studies with different methods are necessary.